A case report of anti‐N‐methyl‐d‐aspartate receptor encephalitis with chromosomally integrated human herpesvirus 6. Issue 1 (5th November 2022) - Iwao, Kazunori; Watanabe, Mitsuru; Mukaino, Takahiko; Fujii, Takayuki; Yamasaki, Ryo; Isobe, Noriko
Abstract: Chromosomally integrated human herpesvirus 6 (ciHHV6) is a condition where HHV6‐DNA is integrated into the host germline genome. ciHHV6 can be misdiagnosed as active HHV6 infection. We report a 30‐year‐old woman presenting with psychological symptoms without a history of immunodeficiency. She had an ovarian teratoma and anti‐ N ‐methyl‐D‐aspartate receptor (NMDAR) antibodies in the cerebrospinal fluid (CSF) with HHV6‐DNA in the serum and CSF. The final diagnosis was anti‐NMDAR encephalitis and ciHHV6 because laparoscopic oophorectomy and immunotherapy ameliorated her symptoms and HHV6‐DNA was detected in her oral mucosa cells. This case suggests the need to assess whether HHV6‐DNA is related to infection or ciHHV6 when HHV6‐DNA is detected in the CSF of patients with encephalitis.